Subjective Well-Being Scarring through Unemployment: New Methods, New Results? - Eberl, Andreas; Collischon, Matthias; Wolbring, Tobias (2021)
Scarring effects of unemployment on subjective well-being (SWB), i.e., negative effects that remain even after workers reenter employment, are well documented in the literature. Nevertheless, the theoretical mechanisms by which unemployment leads to long-lasting negative consequences for SWB are still under debate. Thus, we theorize that unemployment can have an enduring impact mainly through (i) the experience of unemployment as an incisive life event that, for example, affects health and (ii) unemployment as a driver of future unemployment. Using advanced longitudinal modeling that controls for group-specific trends, we estimate SWB scarring through unemployment using German panel data from the Socio-Economic Panel (SOEP). Our results consistently show a large negative effect of unemployment on SWB as well as significant lasting scarring effects (for both men and women as well as for short- and long-term unemployment spells). Further analyses reveal that repeated periods of unemployment drive these effects, implying that there are hardly any adaptations to unemployment that buffer its effect on SWB. We conclude that scarring effects through unemployment mainly work through unemployment increasing the probability of future unemployment. Regarding policy implications, our findings suggest that preventing unemployment, regardless of its duration, is beneficial for individual well-being.<br
Keywords: fixed effects; life satisfaction; panel data; power analysis; unemployment; Gender